Correlating Crack Onset Strain and Cohesive Fracture Energy in Polymer Semiconductor Films - Balar, Nrup; O’Connor, Brendan T (Macromolecules, 2017)
Polymer semiconductors are an attractive material system for flexible and stretchable electronic devices owing to their potentially favorable mechanical attributes. Establishing the thermomechanical behavior of polymer semiconductors is thus an important consideration to ensure successful operation in these applications. One of the most common mechanical characterization methods for these materials is to manipulate the thin films while on an elastomer substrate. A primary measurement with this approach is the film’s crack onset strain (COS), a measure of ductility. It is simple and effective; however, it is a highly qualitative view of film mechanical stability, particularly in flexible device applications. Alternatively, cohesive fracture energy (G c) provides a direct quantitative measure of the mechanical integrity of the film. While fracture energy provides important insight into mechanical stability, it typically requires a more complex measurement method than the film on elastomer tests. Here, we compare the COS using film on elastomer testing, with cohesive fracture energy measured using four-point bending for a range of polymer semiconductor films. The polymers considered have a range of molecular structures and molecular packing characteristics providing a broad representative sample set. The values of G c ranged from 0.4 to 18 J/m2 while COS ranged from 2% to over 100%. We show that COS of the films can be correlated with G c providing support that COS is a valuable measurement to probe the mechanical toughness of polymer semiconductor films. We also discuss the physical characteristics each measurement highlights and the complementary nature of these measurements.